1993
DOI: 10.1111/j.1432-1033.1993.tb18342.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human cytochrome c, oxidase subunits during fetal development

Abstract: Expression of human cytochrome c oxidase (COX) subunits was examined at fetal (20-28 weeks) and adult state by Northern blot hybridization with mRNA from liver, heart, skeletal muscle, and intestine. The data were related to COX and citrate synthase activities and to immunodetected COX subunits (II/III, IV, VIIaH). In liver little changes of COX transcripts are observed from fetal to adult state. In contrast, in heart and skeletal muscle all transcripts of COX subunits increase between 2-20-fold, when related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 57 publications
4
41
1
Order By: Relevance
“…We were able to confirm the tissue-specificity of the isoforms by performing Northern-blot analysis of various rat tissues. Similarly to previous findings in bovine [25,26,44], rat [22] and human [38], we found that the liver isoform of both subunits, VIII and VIa, was expressed at variable levels in liver, brain, lung, skeletal muscle, atria and ventricle tissues, whereas the heart isoform was expressed in the skeletal muscle, atria and ventricle tissues only (results not shown).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…We were able to confirm the tissue-specificity of the isoforms by performing Northern-blot analysis of various rat tissues. Similarly to previous findings in bovine [25,26,44], rat [22] and human [38], we found that the liver isoform of both subunits, VIII and VIa, was expressed at variable levels in liver, brain, lung, skeletal muscle, atria and ventricle tissues, whereas the heart isoform was expressed in the skeletal muscle, atria and ventricle tissues only (results not shown).…”
Section: Resultssupporting
confidence: 71%
“…The heart isoforms of both VIa and VIII increase dramatically as development progresses from the fetal to the adult stage. Although the expression of the heart isoform has previously been shown to be highly up-regulated in bovine (VIa) and human (VIa and VIIa) hearts during development, the fetal hearts in these species already expressed the heart isoform in relatively large amounts [26,38], whereas our results in the rat demonstrated that the fetal heart expressed little (VIa) or no (VIII) heart isoform. The liver isoform was the predominant form of VIa and VIII in the fetal rat heart followed by a significant down-regulation as the rat approached adulthood.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…2000) and at different developmental stages (Bonne et al. 1993). Isoforms enable control of ATP production and the membrane potential across variable conditions in different organs and tissues within an individual (Pierron et al.…”
Section: Speciation Via Mitonuclear Coevolution To Maintain Coadaptationmentioning
confidence: 99%